DESALINASI AIR ASIN MENGGUNAKAN MEMBRAN SELULOSA BAKTERI AKRILAMIDA-ASETAT - Raudhatul Fadhilah (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTClean water crisis that still happening in some parts of the world led to the development of water processing techniques continue to be made. One source of water comes from the oceans which have a high salt density. Water processing techniques that developing rapidly in the processing of salty water is membranes desalination. In this study, the cellulose membrane of acrylamide bacteria was synthesized using the basic ingredients of a banana peel. Escalation of membrane selectivity in absorbing salts and minimizing blockage (fouling) was performed by doping acetic acid into the cellulose membrane of acrylamide bacteria. Measurement by using spectrophotometry UV-Vis technique (λ = 490 nm) on a standard series of NaCl concentration of 0 ppm, 250 ppm, 500 ppm, 2000 ppm obtained line equation y = 0.0002x + 0.0986 R ² = 0.8286. The results showed that the rejection coefficient (R) of bacterial cellulose which is doped with acetic acid was higher (R = 62.15%) than the cellulose acrylamide bacteria without acetic acid (R = 44.65%). Thus, the cellulose membrane of acrylamide bacteria which is doped with acetic acid is more selective thanthe cellulose membrane of acrylamide bacteria without doped with acetic acid. The addition of acetic acid causes the membrane pore tighter, therefore the membrane's ability to absorb the salt also increases.Keywords: acrylamide, saltwater, fouling, membrane, acetate bacterial cellulose